(untitled) (Asian Journal of Medical and Biological Research, 2016)
This study was conducted to investigate the prevalence of common parasitic and infectious diseases of goat at Babugonj upazilla, Barisal, Bangladesh. The study was performed in Veterinary Clinic, ANSVM, PSTU and Upazilla Veterinary Hospital, Babugonj, Barisal during June, 2014 to May, 2015. The diseases were diagnosed on basis of clinical signs, owners statement, general clinical examinations and laboratory diagnosis. A socio-economic survey of 200 destitute women and marginal/poor farmers of Barisal district was also done using a semi-structured questionnaire on their household. 70% of the respondents were females while 30% were males. 65% respondents were involved in agriculture, 13% in own business, 3% in shared business, 2% in govt. service and 17% in non-govt. service. 39% respondents had knowledge about signs of health of goat followed by management (74%), goat diseases (24%), veterinary drugs (20%), animal vaccine (14%) and biosecurity (13%). 53% animal houses were kacha followed by tin (41%) and pukka (2%). Goat received feed from own fodder areas (52%), purchase concentrate (5%) and both (43%). Respondents used tube-well (24%), river (18%), canal (26%) and ponds (32%) as the source of water for their goat. The prevalence of parasitic diseases was 41.33% followed by infectious diseases (39.34%) in goat. The prevalence of parasitic diseases was highest in rainy season 51.28% followed by autumn (41.61%), summer (40.37%) and winter (27.98%). The prevalence of infectious diseases was highest in winter 52.60% followed by autumn (37.55%), summer (37.47%) and rainy season (32.42%). Among viral diseases, prevalence of PPR was highest 8.52% followed by FMD (6.81%), goat pox (2.68%), contagious ecthyma (1.76%) and rabies (0.25%). The prevalence of peste des petits ruminants (PPR) was highest in winter (15.86%). The prevalence of pneumonia was highest 8.71% in whole year among the bacterial diseases. The prevalence of fungal disease (ringworm) was 1.44% in goat. The prevalence of trematodiasis was 12.60% followed by nematodiasis (11.27%), babesiosis (2.18%), tape worm infection (2.03%) and coccidiosis (1.19%). The prevalence of ecto-parasitic diseases was 12.06% .The prevalence of trematodiasis was highest in rainy season (18.01%). The prevalence of babesiosis was highest in summer (3.81%) and coccidiosis in winter (3.81%). The prevalence of ecto-parasitic diseases was lowest in winter (8.88%). The results of the present study will be helpful for scientists, extension service providers and veterinary practitioners for designing appropriate control measures for such diseases of goat. Asian J. Med. Biol. Res. December 2015, 1(3): 449-456